(untitled) (Journal of Applied Oral Science, 2021)
Dual-cured buildup composites and simplified light-cured adhesive systems are mixed with a chemical activator to prevent the incompatibility between them. Objective: To evaluate microshear bond strength (μSBS) and nanoleakage (NL) of three universal adhesives used under buildup composites using different curing modes, at baseline and after 6-months (6m). Methodology: Dentin specimens of 55 molars were assigned to: Clearfil Universal Bond[CFU], Prime&Bond Elect[PBE] and One Coat 7 Universal[OCU]. All-Bond Universal[ABU] and Adper Scotchbond Multi-Purpose[SMP] were used as controls. CFU, PBE, and OCU were: light-cured [LC], dual-cured using a self-curing activator [DC], and self-cured, using a self-curing activator and waiting for 20 min [SC]. Upon the application of the adhesive, transparent matrices were filled with a dual-cured buildup composite and light cured, then tested in mSBS. For NL, the specimens were submersed in ammoniacal silver nitrate and sectioned to observe under the SEM. Three-way ANOVA and Tukey's test were applied (α=0.05). Results: OCU/LC-PBE/LC resulted in higher mean μSBS than ABU/LC. For SMP/DC higher mean μSBS were obtained than for both CFU/DC and OCU/DC (baseline). No universal adhesive was significantly affected by curing mode or storage time. CFU, PBE, and OCU did not undergo significant changes in any curing mode (p>0.05). NL (baseline) PBE/LC resulted in higher %NL compared to ABU/LC. SMP/DC resulted in higher %NL than CFU/DC-OCU/DC. CFU/LC/DC resulted in lower %NL than CFU/SC. PBE/SC resulted in lower %NL than PBE/DC. OCU/LC/SC showed lower %NL than OCU/DC. OCU showed significant lower %NL than CFU and PBE. All CFU groups, as well as OCU/SC, resulted in increased %NL at 6m when compared with baseline. Conclusion: For universal adhesives used in etch-and-rinse mode, self-cured activator and different curing modes did not influence μSBS. However, some interactions were observed for NL, but this influence was material-specific.